QUANTITATIVE ANALYSIS OF STRUCTURAL ALTERATIONS IN THE CHOROID OF PATIENTS WITH ACTIVE BEHCET UVEITIS - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2018)
Purpose: To quantitatively analyze in vivo morphology of subfoveal choroid during an acute attack of Behcet uveitis. Methods: In this prospective study, 28 patients with Behcet uveitis of <= 4-year duration, and 28 control subjects underwent enhanced depth imaging optical coherence tomography. A novel custom software was used to calculate choroidal stroma-to-choroidal vessel lumen ratio. Subfoveal choroidal thickness was measured at fovea and 750 mu m nasal, temporal, superior, and inferior to fovea. Patients underwent fluorescein angiography and indocyanine green angiography. Receiver operating characteristic curve and area under the curve were computed for central foveal thickness. The eye with a higher Behcet disease ocular attack score 24 was studied. The main outcome measures were choroidal stromato-choroidal vessel lumen ratio and choroidal thickness. Results: The mean total Behcet disease ocular attack score 24, fluorescein angiography, and indocyanine green angiography scores were 7.42 +/- 4.10, 17.42 +/- 6.03, and 0.66 +/- 0.73, respectively. Choroidal stroma-to-choroidal vessel lumen ratio was significantly higher in patients (0.413 +/- 0.056 vs. 0.351 +/- 0.063, P = 0.003). There were no significant differences in subfoveal choroidal thickness between patients and control subjects. Choroidal stroma-tochoroidal vessel lumen ratio correlated with retinal vascular staining and leakage score of fluorescein angiography (r = 0.300, P = 0.036). Central foveal thickness was significantly increased in patients (352.750 +/- 107.134 mu m vs. 263.500 +/- 20.819 p.m, P < 0.001). Central foveal thickness showed significant correlations with logarithm of minimum angle of resolution vision, Behcet disease ocular attack score 24, total fluorescein angiography score, retinal vascular staining and/or leakage and capillary leakage scores of fluorescein angiography, and total indocyanine green angiography score. At 275 mu m cutoff, diagnostic sensitivity and specificity of central foveal thickness for acute Behcet uveitis were 89% and 72%, respectively (area under the curve = 0.902; 95% CI = 0.826-0.978, P < 0.001). Conclusion: There was choroidal stromal expansion which was not associated with thickening of the choroid. Central foveal thickness may be used as a noninvasive measure to assess inflammatory activity in early Behcet uveitis.
Keywords: Behcet uveitis; central foveal thickness; choroidal stroma; choroidal vessel lumen; enhanced depth imaging; fluorescein angiography; indocyanine green angiography; optical coherence tomography; subfoveal choroidal thickness; OPTICAL COHERENCE TOMOGRAPHY; INDOCYANINE GREEN ANGIOGRAPHY; FLUORESCEIN ANGIOGRAPHY; VISUAL-ACUITY; RETINAL VASCULITIS; DISEASE; EYES; INFLAMMATION; INVOLVEMENT; THICKNESS